2020
DOI: 10.2147/dmso.s281527
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect and Mechanism of <em>Ganoderma lucidum</em> Spores on Alleviation of Diabetic Cardiomyopathy in a Pilot in vivo Study</p>

Abstract: Background Ganoderma lucidum spores (GLS) exhibit disease prevention properties, but no study has been carried out on the anti-diabetic cardiomyopathy property of GLS. The aim of this study was to evaluate the hyperglycemia-mediated cardiomyopathy protection and mechanisms of GLS in streptozotocin (STZ)induced diabetic rats. Methods Male SD rats were randomly divided into three groups. Two groups were given STZ (50 mg/kg, i.p.) treatment and when their fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…These results showed that GLPP-treated subjects had lower oxidative stress suggesting the GLPP could be potential for preventing development of oxygen stress-induced inflammation. The decrease of MDA and significant increase of SOD in the GLPP treatment group were also reported in atherosclerotic (26) and type 2 diabetes mellitus rats studies (27,28). In human, with the treatment of GLPP, subjects with atrial fibrillation (24) and stable angina pectoris (17) showed a decrease of MDA level.…”
Section: Discussionsupporting
confidence: 60%
“…These results showed that GLPP-treated subjects had lower oxidative stress suggesting the GLPP could be potential for preventing development of oxygen stress-induced inflammation. The decrease of MDA and significant increase of SOD in the GLPP treatment group were also reported in atherosclerotic (26) and type 2 diabetes mellitus rats studies (27,28). In human, with the treatment of GLPP, subjects with atrial fibrillation (24) and stable angina pectoris (17) showed a decrease of MDA level.…”
Section: Discussionsupporting
confidence: 60%
“…Certain natural compounds can ameliorate cardiac inflammation by directly modulating inflammatory responses. Probiotics, fungi, and medicinal plants exert an anti-inflammatory action via downregulation of TLR4 expression ( Chiang et al, 2021 ) and reduction of IL-1β, TNFα, MCP-1, and TGFβ ( Wang et al, 2018 ; Shaher et al, 2020 ), subsequently preserving cardiac structure and function in T1DM rodents. Moreover, hederagenin, a plant extract, improves cardiac function by diminishing secretion of pro-inflammatory cytokines and decreasing NF-κB transcriptional activity in db/db mice ( Li Y. et al, 2019 ).…”
Section: Therapeutic Strategies For Prevention Of Dcm By Targeting Inflammationmentioning
confidence: 99%
“…Several extracts of Ganoderma lucidum showed amelioration in this progress in a review [ 50 ], e.g., one study [ 51 ] showed that proteoglycan isolated from Ganoderma lucidum fruiting bodies shows protection renal morphology in diabetic mice in a dose-dependently (75, 250, and 450 mg/kg) manner during a 8-week treatment. According to previous research, the mechanism appears also via directly elimination reactive oxygen species, suppresses lipid peroxidation, and indirectly scavenges the radicals via activating antioxidant enzyme systems and chelation with metal ion by forming crossbridge between carboxyl groups decreasing reactive oxygen species generation [ 52 60 ]. This study showed that the expressions of the inflammatory factors IL-6, IL-1 β , and TNF- α in the diabetic group were significantly increased, while they were reduced significantly after GLP treatment.…”
Section: Discussionmentioning
confidence: 99%